2018
DOI: 10.3390/cli6040086
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus of Weather Extremes to Agriculture Production Indexes and the Future Risk in Ghana

Abstract: The agricultural industry employs a large workforce in Ghana and remains the primary source of food security and income. The consequences of extreme weather in this sector can be catastrophic. A consistent picture of meteorological risk and adaptation patterns can lead to useful information, which can help local farmers make informed decisions to advance their livelihoods. We modelled historical data using extreme value theory and structural equation modelling. Subsequently, we studied extreme weather variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…The rainy season spans from April to mid-July and October and temperatures hoover around 24˚C and 28˚C all year round. The rainfall of Accra is usually down below 800 mm (31.5 in) [26]. The months that Accra experiences heavy rainfall are May and June.…”
Section: Accra Metropolitan Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The rainy season spans from April to mid-July and October and temperatures hoover around 24˚C and 28˚C all year round. The rainfall of Accra is usually down below 800 mm (31.5 in) [26]. The months that Accra experiences heavy rainfall are May and June.…”
Section: Accra Metropolitan Areamentioning
confidence: 99%
“…The months that Accra experiences heavy rainfall are May and June. Occasionally the first half of July experiences also heavy rainfall [26]. Odaw River flows through Accra with approximately 60% of the Metropolis living in its catchment [27].…”
Section: Accra Metropolitan Areamentioning
confidence: 99%
“…West Africa was selected for this study because the region has experienced a number of severe weather events with devastating socio-economic impacts (Schaer and Hanonou, 2017;Salack et al, 2018;Gbode et al, 2019). In addition, climate change induced extreme weather conditions are expected to significantly affect crop production in the region (Sultan and Gaetani, 2016;Ibn Musah et al, 2018). Changing climate is also expected to cause a substantial drop in hydropower production in West Africa (Yang et al, 2018;Falchetta et al, 2019) and increase the risk of infectious disease outbreaks (Bell et al, 2018;Thomson et al, 2018).…”
Section: Background and Contextmentioning
confidence: 99%
“…Studies from different parts of the world suggest that high rainfall events can lead to crop yield reduction. Studies from Ghana revealed negative impact on crop yields due to heavy rainfall events [53,54].…”
Section: Rainfall Variability Analysismentioning
confidence: 99%